Balancing Work – Life and Personal – Life Expectancies: Insights from Public and Private Sector Banks (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Banking sector is strength for the economic development of any country and the women is playing an important role in functioning of the banking sector. At present, banks are creating more opportunities for women employees. Most of the women prefer jobs in banks because they are more attractive and comfortable. Currently, women employees are facing challenges in fulfilling the responsibilities both in professional life and work life. The present study is to know about the personal life expectations and work-life expectations of women employees working in the public and private sector banks in Visakhapatnam. A sample of 120 respondents was selected using simple random sampling. Data were collected through structured questionnaires based on a five-point Likert scale. Statistical tools including descriptive statistics, ANOVA, and multiple regression analysis were employed. The findings reveal significant differences in expectations across sectors and demographic categories. Regression analysis further indicates that age, marital status, work experience, and type of bank significantly influence work–life and personal–life expectations. The study provides managerial insights for designing gender-sensitive workplace policies.